PERAN KOMUNIKASI PEMASARAN TERPADU MELALUI EKUITAS MEREK TERHADAP KINERJA PEMASARAN SEKOLAH TINGGI ILMU EKONOMI (STIE) BINA BANGSA BANTEN - Kurniadin, Adi; Mukhsin, Moh. (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2018)
his study analyzes the effect of integrated marketing communication variables on brand equity to improve marketing performance. This research was conducted at Sekolah TinggiIlmu Ekonomi (STIE) Bina Bangsa Banten. Based on the results of the literature review there is a positive influence on brand equity and marketing performance and this is supported by integrated marketing communication variables such as the use of appropriate advertising media, the application of good personal sales, the promotion of appropriate sales and effective direct marketing. Thus there are seven hypotheses proposed: This research uses 108 questionnaires collected from STIE Bina Bangsa Banten as the sample. The questionnaire data were analyzed with Structural Equation Modeling (SEM) analysis tool in AMOS 22.0program to test the causality relationship of the proposed hypotheses. The results of data analysis show that the research model has a good fit/fit and all research hypotheses can be proven. The test of the proposed hypothesis shows the result that all hypotheses have met the specified condition of CR> 2.00 with probability (p)) <0.05. The conclusion is that advertising, personal selling, sales promotion, and direct marketing have a positive effect on brand equity and the brand equity has a positive effect on marketing performance, and advertising and direct marketing have a positive effect on marketing performance. This study provides some limitations of the research and future research agenda that can be done as further research.